827 Long-term milrinone therapy in children with DCM phenotypes: safety, efficacy, and impact on recovery of cardiac function. (17th August 2022) - Brown, Sam; Nolan, Oscar; Poole, Esther; Kidd, Justine; Cassidy, Jane; Botha, Phil; Chaudhari, Milind
Abstract : Aims: The management of paediatric decompensated dilated cardiomyopathy (DCM) is challenging. Mechanical circulatory support (MCS) and heart transplantation (HTx) are lifesaving but limited by availability, safety, and suitability in small children. Milrinone has unique inodilatory properties useful in acute heart failure (HF) treatment but evidence for its prolonged use is lacking. Our objective was to evaluate the safety and efficacy of long-term milrinone therapy and its impact on the recovery of cardiac function in children with severe HF due to DCM. Methods: A single-centre retrospective study (2008-2021) of children (<16 years) with severe HF due to DCM treated with intravenous milrinone for ≥7 consecutive days. Patients with structural heart disease were excluded. Escalation to MCS and HTx occurred in the event of deterioration. Clinical evaluation, serial echocardiograms and biomarkers assessed recovery. Results: Forty-eight patients were identified, with a median age of 3.3 months (Interquartile range IQR 1.0-18.1), a weight of 5.7kg (IQR 4.3-10.1) and an ejection fraction of 25.7% (±9.4). All patients were admitted to intensive care and 83% required invasive ventilation. Nineteen were male (40%) and 38% weighed under 5kg. Myocarditis (n=19) and idiopathic DCM (n=17) were the most common diagnoses, four others had defined causative genetic mutations and three had anthracycline-induced DCM ( table 1 ). The median milrinone infusion duration was 24 days (IQR 10-48, range 7-290). During this period, paired fractional shortening (FS) significantly increased from 12.4% (±4.99) to 16.8% (±4.39) (p<0.001) whilst concurrently NT-proBNP dropped from 38201 to 4727 (p<0.001) in patients who later recovered echocardiographic cardiac function. The only recorded adverse effects of long term milrinone infusion were line infections (n=4) and hypotension (n=1), neither of which led to the cessation of therapy. Seven patients required escalation to MCS, five of which were ventricular assist devices (VAD). The median follow-up period was 2.4 years (IQR 1.0-4.4), there were ten deaths, five heart transplantations and 57% (n=27) recovered a normal FS measurement (≥26%). ( table 1 ) Of the deaths, five occurred on milrinone after complex, lengthy first admissions, one on VAD, three upon readmission, and one patient died from pneumonia after initially recovering ( figure 1 ). The median time to recovery was 13.3 months (IQR 9.0-24.4) ranging from 1.3 to 43.9 months. Myocarditis (63%) and those under 5kg (67%) had the most recovered patients, but there was no significant difference in this recovery by aetiology, weight, or age. Conclusion: Long-term intravenous milrinone therapy is safe and effective in children with decompensated HF due to DCM. It was able to successfully bridge over half of patients to recovery and many of the remaining to MCS or HTx. This treatment protocol should be an integral part of advanced heart failure management, particularly in small infants and children where MCS and HTx options are limited.